Philo-Germanism without Germans in Romania after 1989. (November 2015) - Cercel, Cristian
This article argues that positive representations of the German minority in post-1989 Romania, discernible in specific memory and identity discourses, are linked to an internalized self-orientalizing view of Romanianness and to a symbolic wish to "belong to Europe, " present in Romanian society and displayed on the Romanian political scene. In other words, it maintains that a phenomenon describable as "philo-Germanism without Germans" in contemporary Romania is tightly connected with the production and reproduction of symbolic geographies whose aim is to insert Romania into the "civilized" Western/European world.